SEPT9 and PAI-1 are immunohistochemical biomarkers of the hepatocellular carcinoma immune microenvironment - Eundong Park; Xin Wang; Nusret Bekir Subasi; Michel Kmeid; Paul J. Higgins; Anne Chen; Hwajeong Lee (Discover Oncology)
Abstract Background Septin 9 (SEPT9) interacts with multiple oncogenic proteins and is expressed abnormally in several cancers, including hepatocellular carcinoma (HCC). Plasminogen activator inhibitor-1 (PAI-1) promotes tumor formation and progression by modulating the tumor immune microenvironment. CXCR2+ immune cells play a crucial role in HCC formation, progression, and prognosis. The relationship between SEPT9 and PAI-1, and their impact on the HCC immune microenvironment remains unclear. Methods Expression levels of SEPT9 and PAI-1 were evaluated by immunohistochemistry (IHC) in HCC and background benign liver (n = 76). Their IHC results were examined for relationships with immune cell markers (CXCR2, CD3, CD15, CD68, and CD163), clinical parameters, and survival outcomes. Results Higher grade HCC expressed SEPT9 and PAI-1 more frequently. SEPT9 and PAI-1 expression were associated with each other. PAI-1(+) HCCs had higher intratumoral CXCR2, CD3, CD15, CD68, and CD163 expression compared to PAI-1(−) HCCs, while SEPT9 expression correlated with greater CXCR2+ and CD15+ cell counts in tumor. SEPT9(+) HCC patients had shorter OS, although SEPT9 was not an independent prognostic factor. Conclusion SEPT9 is associated with PAI-1, a pro-tumorigenic protein. Both SEPT9 and PAI-1 are linked to advanced HCC grades. SEPT9 and PAI-1 positive HCCs have distinct CXCR2+ immune cell landscapes. Further investigation is needed to elucidate a possible SEPT9/PAI-1 interaction and the clinical utility of SEPT9 IHC in HCC.